Reduction of salt intake: time for more action - Jones, Erika S.W.; Lee, Hae Young; Khan, Nadia; Charchar, Fadi J.; Williams, Bryan; Chia, Yook Chin *; Tomaszewski, Maciej (Lippincott, Williams & Wilkins, 2022)
EuropeanSociety of Cardiology (ESC)/European Society of Hypertension (ESH), the WHO and other organizations recommend a goal of reducing salt intake to less than 5g/day, but the achievement rate is low [1–3]. Populations in almost all countries in the world exceed this threshold, with Asian populations having an average daily salt intake as high as 10g. The recent publication by the World Hypertension League (WHL), Resolve to Save Lives (RTSL) and International Society of Hypertension (ISH) provides a drive to create momentum in the global ‘Call to Action’ [4] to lower salt intake around the world.